Industry 5.0. Present or Future? - Ficzere, Péter (Design of Machines and Structures, 2024)
Industry 5.0 represents a significant evolution in industrial development, building upon the technological foundations of Industry 4.0. Highlighting human-centric and sustainable approaches, Industry 5.0 aims to integrate human creativity and technology seamlessly. While previous industrial revolutions were marked by technological advancements –such as steam engines, electricity, and digital transformation– Industry 5.0 emphasizes the synergy between humans and machines. This collaboration is expected to drive production efficiency and ethical practices in industry, creating a more resilient and human-focused future. This paper investigates the need of education systems to prepare the students to i5.0.